Peran Perguruan Tinggi dalam Penurunan Emisi Gas Rumah Kaca Melalui Pengelolaan Sampah Kantin - Tuani Lidiawati Simangunsong (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2018)
Higher education institutions can play a role in reducing greenhouse gas emissions through solid waste management. One of the solid waste sources in the campus is a canteen. Surabaya University (Ubaya) is one of the higher education institutions in Surabaya has two canteens that generate waste everyday. In the canteen waste is separated into food waste, food cardboards and plastic bottles. Food waste and food cardboards has not processed yet. A research related to the potential utilization of canteen waste need to be  conducted. The aims of the research are  determining the amount of organic waste generation in Ubaya canteen and calculating the greenhouse gas that can be derived if organic waste is processed into biogas. The scope of calculation was CH4 generation. The research is conducted in the Keluwih Canteen.  The estimation of canteen waste is taken for ten days. The surveys conducted during November 2017. The calculation of green house emission from solid waste was referred to Intergovernmental Panel on Climate Change (IPCC)  2006 guidelines.  The results of the research indicated that the average quantity of food waste is 6,3 kgs per day, 5  kgs per day of food cardboards and  Surabaya University can contribute to reduce green house gas emission (CH4) about 0,85 kg CH4 per day.